COMPARATIVE ANALYSIS OF PHISHING WEBSITE PREDICTION CLASSIFICATION ALGORITHM USING LOGISTIC REGRESSION, DECISION TREE, AND RANDOM FOREST - Al Rifqi, Muhammad Fandru; Dina, Mauli; Anita, Anita; Nababan, Marlince N.K; Aisyah, Siti (Sean Institute, 2022)
Almost all daily activities are poured into the Internet, and users interact by having a personal account that is linked to the world's data, by giving each user access to view various information around the world through the website. However, with the increasing number of users accessing the internet, the confidentiality of internet users' data is increasingly vulnerable to being stolen by irresponsible individuals or groups. Phishing is an attack in which an attacker tries to steal confidential information from a target person by sending a fake link. Attackers steal personal information entered by users on fake websites. In comparing the prediction classification of phishing websites using the logistic regression algorithm, decision tree